EVALUATION OF SYNERGISTIC EFFECT OF EVAPORATIVE COOLING SYSTEM AND POTASSIUM PERMANGANATE ON EXTENDING THE SHELF LIFE AND QUALITY OF PLANTAIN - SAMUEL, OYEWOLE OMONIYI; K, OGUNGBEMI; O, ILORI A; O, IBITOYE; BT, AYANGBEMI (Innovare Journal of Agricultural Sciences, 2023)
Background: Plantain is a climacteric fruit, which means that as it ripens, it increases its respiration rate and ethylene production. Therefore losses are recorded along its production chain value. Post-harvest loss is a major problem limiting the production of plantain in African due to unavailability of established storage conditions that can guarantee long shelf life. In the quest of extending the shelf life and quality of plantain, this study was carried out to evaluate the synergistic effect of Evaporative cooling system (ECS) and Potassium permanganate (KMnO4). Methods: Unripe plantain fruit were stored under four different condition, ECS, KMnO4 only, ECS with KMnO4 and a control. The storage was done for a period of 12 days with laboratory analysis carried out through this period to analyze the quality of the stored fruits. The pH, weight loss, Total soluble solid (TSS), peel color, Total titratable acid, firmness test and dry matter was carried out. Result: The pH, which is a major factor in determining the degree of ripening of fruit was obtained to be 4.85, 4.94, 5.00 and 5.77 for control, KMnO4, ECS and ECS with KMnO4 storage condition respectively. Also, the TSS which is also directly proportional to the degree of ripeness was recorded to be 24.00, 21.00, 12.10 and 10.80 for control, KMnO4, ECS and ECS with KMnO4 storage condition respectively. The least percentage weight loss was obtained in ECS with KMnO4 storage condition which is favorable to a better firmness result. 31%, 15.13% and 11.11% weight loss was obtained in control, KMnO4 and ECS storage condition. After day 6 of storage, the plantain fruits in ECS and ECS with KMnO4 ¬¬storage condition maintained their stage 1 characteristics as different from what was obtainable in control and KMnO4 storage. At the end of the storage period, the quality of the stored plantain fruits stored in ECS with KMnO4 was examined to be better in color, firmness, weight loss, pH, TSS and dry matter. Conclusion: When compared to the individual performances of KMnO4 and ECS, it can be concluded that the synergistic effect further extend the shelf life and quality of plantain fruits.